Antimalarial, antiplasmodial and analgesic activities of root extract of Alchornea laxiflora - Jude E. Okokon; Nkemnele Bensella Augustine; Dinesh Mohanakrishnan (Taylor & Francis Group, 2017)
Context: Alchornea laxiflora (Benth.) Pax. & Hoffman (Euphorbiaceae) root decoctions are traditionally used in the treatment of malaria and pain in Nigeria. Objective: To assess the antimalarial, antiplasmodial and analgesic potentials of root extract and fractions against malarial infections and chemically-induced pains. Material and methods: The root extract and fractions of Alchornea laxiflora were investigated for antimalarial activity against Plasmodium berghei infection in mice, antiplasmodial activity against chloroquine sensitive (Pf 3D7) and resistant (Pf INDO) strains of Plasmodium falciparum using SYBR green assay method and analgesic activity against experimentally-induced pain models. Acute toxicity study of the extract, cytotoxic activity against HeLa cells and GCMS analysis of the active fraction were carried out. Results: The root extract (75-225 mg/kg, p.o.) with LD50 of 748.33 mg/kg exerted significant (p < 0.05-0.001) antimalarial activity against P. berghei infection in suppressive, prophylactive and curative tests. The root extract and fractions also exerted moderate activity against chloroquine sensitive (Pf 3D7) and resistant (Pf INDO) strains of P. falciparum with the ethyl acetate fraction exerting the highest activity with IC50 value of 38.44 ± 0.89 μg/mL (Pf 3D7) and 40.17 ± 0.78 μg/mL (Pf INDO). The crude extract was not cytotoxic to HeLa cells with LC50 value >100 μg/mL. The crude extract and ethyl acetate fraction exerted significant (p < 0.05-0.001) analgesic activity in all pain models used. Discussion and conclusions: These results suggest that the root extract/fractions of A. laxiflora possess antimalarial, antiplasmodial and analgesic potentials and these justify its use in ethnomedicine to treat malaria and pain.